Oxysophocarpine Prevents the Glutamate-Induced Apoptosis of HT–22 Cells via the Nrf2/HO–1 Signaling Pathway - Ruiying Yuan; Dan Gao; Guibing Yang; Dongzhi Zhuoma; Zhen Pu; Yangzhen Ciren; Bin Li; Jianqing Yu (Current Issues in Molecular Biology)
Oxysophocarpine (OSC), a quinolizidine alkaloid, shows neuroprotective potential, though its mechanisms are unclear. The aim of the present study was to investigate the neuroprotective effects of OSC through the nuclear factor erythroid 2−related factor 2 (Nrf2)/ heme oxygenase−1 (HO–1) signaling pathway using the HT–22 cell line. Assessments of cell viability were conducted utilizing the 3−(4,5−dimethylthiazol−2−yl)−2,5−diphenyltetrazolium bromide (MTT) assay. Assessments of oxidative stress (OS) were conducted through the quantification of reactive oxygen species (ROS). The integrity of the mitochondrial membrane potential (MMP) was scrutinized using fluorescent probe technology. Apoptosis levels were quantified using terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining. The trafficking of Nrf2 within the cell nucleus was examined through immunofluorescence analysis. Furthermore, Western blotting (WB) was applied to evaluate the expression levels of proteins implicated in apoptosis and the Nrf2/HO–1 pathway. To further probe the influence of OSC on the overexpression of antioxidant enzymes, cells were subjected to transfection with HO–1 siRNA. The results showed that OSC inhibited glutamate-induced OS, as evidenced by reduced cell viability and ROS levels. Furthermore, the apoptotic condition induced by glutamate in HT–22 cells was significantly reduced following OSC treatment. More interestingly, the Nrf2/HO–1 signaling pathway was upregulated following OSC treatment. These results suggest that OSC can exert neuroprotective effects by regulating the Nrf2/HO–1 pathway to inhibit neuronal cell apoptosis, potentially aiding in the treatment of neurodegenerative diseases.